Uterine Prolapse Complicating the 3rd Trimester of the Pregnancy: A Case Report - Seçilmiş Kerimoğlu, Özlem; İncesu, Feyza Nur and Tazegül, Aybike and Doğan, Nasuh Utku and Yılmaz, Setenay Arzu and Çelik, Çetin (Gynecology Obstetrics & Reproductive Medicine, 2012)
Uterine prolapse is extremely rare during pregnancy. Prolapse etiology depends on many factors, such as advanced age, multiparity, difficult vaginal delivery and increased body mass index. This condition may be complicated by cervical desiccation and ulceration, preterm labor, obstructive labor and even maternal death. We report a case of uterine prolapse which developed during pregnancy. A 40-year-old woman gravida 5 para 4 with stage 3 uterine prolapse was admitted to hospital with pelvic pain and urinary tract infection at 35th week of the gestation. A cesarean section was performed at 38th week of the gestation because of profound cervical bleeding due to the edematous, ulcerated, desiccated cervix. Postnatally, the uterine prolapse spontaneously recovered. Uterine prolapse that occurs during the pregnancy should be managed using a conservative approach. It seems that severely desiccated cervix cause profound bleeding and cesarean delivery should be preferred.